Evolution of public administration of book publishing in Russia (the middle of the XVI century - 1980s) - D. G. Zalevskaya (RUDN Journal of Public Administration, 2018)
In this article author examines the history of public administration of book publishing since the birth of mass printing in the middle of the XVI century to the stagnant crisis of 1980s. During this period of time the national book publishing has changed in the legal ﬁeld, in copyright and censorship of the press, and in the structure of management, in establishment and functioning of supervisory authorities. In the 1980-s public administration of book publishing was an eﬀective centralized system of regulating the book publishing and book distribution throughout the country as a whole. But the stagnant crisis of 1980-s, which took place in many sectors of the Soviet economy, demanded reform and change.